Pengembangan Media KOBAR Digital untuk Meningkatkan Kemampuan Qirā’ah Fahmiyyah dan Motivasi Belajar Siswa Sekolah Dasar - Afkar, Nafa Rizqil; Finurika, Isna; Rasikh, Fahrur (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to develop a digital KOBAR (Arabic Comics) medium and test its effectiveness in improving reading comprehension (qirā’ah fahmiyyah) and learning motivation among elementary school students. The study employed the 4D development model (Define, Design, Develop, and Disseminate) with a limited test sample of 17 students at SDN Banjarwati, Paciran, and engaged two expert validators (a subject-matter expert and a media expert). Data were collected using expert-validation instruments, reading comprehension tests (pre- and post-tests), and an ARCS-model motivation questionnaire. Data analysis was conducted by calculating the percentage of feasibility scores for the validation data, applying Richard R. Hake’s N-Gain formula to measure learning gains, and analyzing the percentage scores for motivation data. The expert validation results indicated that the media was in the “highly feasible” category with a score of 92.5%. The effectiveness test showed an improvement in learning outcomes, with an N-Gain value of 0.58, which falls into the “moderate” category. Furthermore, the results of the learning motivation questionnaire indicated a “very high” category, reaching a percentage score of 81.91%. Thus, KOBAR Digital is deemed suitable and effective as an adaptive Arabic language learning medium accessible via laptops, computers, or smartphones.